2018
DOI: 10.1111/apa.14323
|View full text |Cite
|
Sign up to set email alerts
|

Waist‐to‐height ratio remains an accurate and practical way of identifying cardiometabolic risks in children and adolescents

Abstract: The WHtR was a superior and practical screening tool for detecting CMR in this paediatric population, as it provided comparable accuracy to other methods and just required a simple calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 21 publications
0
41
0
3
Order By: Relevance
“…Along those lines, it is suggested that researchers adhere to the Consensus on Exercise Reporting Template when designing their study and reporting exercise programme information from their clinical trials 104. Sixth, while none of the studies included waist-to-height ratio as an outcome and it was not part of our a priori protocol, future original studies may want to consider the inclusion of such given that it has been shown to be an accurate predictor105 and correlate106 of cardiometabolic risk in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Along those lines, it is suggested that researchers adhere to the Consensus on Exercise Reporting Template when designing their study and reporting exercise programme information from their clinical trials 104. Sixth, while none of the studies included waist-to-height ratio as an outcome and it was not part of our a priori protocol, future original studies may want to consider the inclusion of such given that it has been shown to be an accurate predictor105 and correlate106 of cardiometabolic risk in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The physical examination was carried out by two trained investigators who measured weight and height for calculating BMI and BMI z-score [4,29], and the waist circumference (after gently exhaling, at the narrowest part between the lower rib and the iliac crest using a non-elastic flexible tape, recorded to the nearest 0.1 cm) and the waist to height ratio (WtHR) [30] were also calculated. Systolic and diastolic blood pressure (BP) was recorded before blood sampling with the subject in a sitting position and after a minimum of 5 min of acclimation.…”
Section: Study Procedures and Assaysmentioning
confidence: 99%
“…Although many authors have produced specific WHtR boundary values for populations (24,27,61,62) , many suggest that the simple boundary value of 0•5 can be used to indicate increased risk and used universally for primary screening (29) . Since it was first advocated in 2006 (63) , the simple message 'Keep your waist to less than half your height' has been recommended often (20,34,(64)(65)(66) .…”
Section: Very Simple Screening Based On Waist-to-height Ratio 0•5: Thmentioning
confidence: 99%
“…More than 20 years ago, a boundary value of WHtR 0•5 was first suggested as a risk assessment tool and this translates into the simple message 'keep your waist to less than half your height' (1,(11)(12)(13) . Studies in many populations have supported the premise that WHtR is a simple and effective anthropometric index to identify health risks in adults of all ages (6,7,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and in children and adolescents (26)(27)(28)(29) . Not only does WHtR have a close relationship with morbidity, but also it has a clearer relationship with mortality compared with BMI (13,30) .…”
mentioning
confidence: 99%